Facing your fears in schools: using the ADIS/ASA to characterize anxiety and intervention outcomes in students with autism or suspected autism - Reaven, Judy; Cosgrove, Kelly T.; Losh, Ainsley; Nickles, Sarah; Kerns, Connor M.; Pickard, Katherine; Blakeley-Smith, Audrey; Hayutin, Lisa; Meyer, Allison T.; Middleton, Caitlin; Reyes, Nuri M.; Boles, Richard E. (Frontiers in Psychiatry, 2025)
BackgroundAutistic youth are at higher risk of developing anxiety compared to their peers, with as many as 40% experiencing clinical anxiety. Emerging research suggests that these rates are an underestimate as distinct presentations of anxiety (e.g., fear of change, idiosyncratic fears) are often not recognized. CBT is a well-established approach for managing anxiety in autistic youth, but many have difficulty accessing these interventions. School-based CBT programs, like Facing Your Fears in Schools (FYF-S), have shown effectiveness in reducing anxiety in autistic students and may increase access to care. The Anxiety and Related Disorders Interview Schedule for DSM-5 with Autism Spectrum Addendum is a semi-structured interview that captures both DSM-5 and distinct presentations of anxiety. This study aimed to: 1) characterize a subsample of students with autism or suspected autism and anxiety and 2) examine effectiveness of FYF-S using the ADIS/ASA.MethodsThis study utilized a subsample of students (N=37; ages 7-14) from a larger Type 1 hybrid-effectiveness trial who had either autism or suspected autism. Students were randomized to either FYF-S or Usual Care (UC). Caregivers completed the ADIS/ASA at baseline and post-intervention. The ADIS/ASA was administered by clinicians rigorously trained to reliability and masked to condition.ResultsStudents had both DSM-5 and distinct anxiety diagnoses at Time 1. Further, students in FYF-S demonstrated significant reductions in anxiety compared to UC, as evidenced by fewer anxiety diagnoses overall and significant improvement in total anxiety.ConclusionThis is the first school-based study using the ADIS/ASA to characterize anxiety and measure outcomes in autistic students. Overall, results indicate that FYF-S may be a promising school-based intervention for autistic youth.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT03685474, identifier NCT03685474.